Relasi Mahkamah Konstitusi dengan Mahkamah Agung: Masalah-Masalah dan Cara Penanggulangannya - Zaka Firma Aditya; Abdul Ghofar (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2023)
The issue of the lack of harmony between the Constitutional Court (MK) and the Supreme Court (MA) has often raised public concerns. This prompts a question: What causes the lack of harmony between these two institutions? In fact, between 2009 and 2018, there were five events that intensified this strained relationship, including the cases of remaining votes, the post-conflict local election in Kotawaringin Barat, the Doctor Bambang case, online transportation case n, and the DPD candidate members’ case. As such, this research formulates the research problem as follows: (1) What is the current relationship between MK and MA in Indonesia? (2) What is the relationship between the Constitutional Court and the Supreme Court in other countries? and (3) What efforts can be made to improve the relationship between these two institutions? This research follows a doctrinal approach and utilizes a combination of statutory, conceptual, and case-based methods. This research concludes that the relationship between the MK and the MA, from 2009 until now, has been characterized by disharmony, evidenced by the resolution of five different legal cases. Similar conflicts between the Constitutional and Supreme Court have also emerged in Germany, Italy, and Poland. However, only the Italian Constitutional Court and Supreme Court have openly engaged in conflicts. To improve relations in the short term, the two institutions need to reach an agreement to avoid making conflicting decisions. In the long run, it becomes necessary to amend the 1945 Constitution to centralize the review process within the Court, with the Chief Justice of the MK concurrently serving as the Chief Justice of the MA.AbstrakIsu kurang harmonisnya Mahkamah Konstitusi (MK) dengan Mahkamah Agung (MA) kerap menjadi perhatian publik. Hal ini menimbulkan pertanyaan, apa penyebab kurang harmonisnya kedua lembaga tersebut? Bahkan sejak tahun 2009 hingga 2018, ada lima peristiwa yang memperburuk hubungan tersebut seperti pada kasus sisa suara, pemilukada Kotawaringin Barat, Dokter Bambang, Angkutan Daring, dan calon anggota DPD. Oleh karenanya, rumusan masalah penelitian ini yakni (1) bagaimana relasi MK dengan MA di Indonesia saat ini? (2) Seperti apa relasi MK dengan MA di negara lain? dan (3) Apa upaya yang dapat dilakukan untuk memperbaiki hubungan kedua lembaga tersebut? Penelitian ini merupakan penelitian doktrinal, dengan pendekatan undang-undang, pendekatan konseptual, dan pendekatan kasus. Penelitian ini menyimpulkan bahwa hubungan MK dan MA sejak tahun 2009 sampai saat ini kurang harmonis ditandai dengan adanya lima kasus hukum yang diputus berbeda. Konflik antara MK dan MA juga terjadi di Jerman, Italia, dan Polandia. Meskipun, hanya MK dan MA Italia yang melakukan konflik secara terbuka. Selanjutnya, untuk memperbaiki hubungan, dalam jangka pendek, kedua lembaga perlu membuat kesepakatan untuk menahan diri tidak membuat putusan yang berbeda. Dalam jangka panjang, perlu dilakukan amendemen UUD 1945 yang menyatukan pengujian berada di MK, serta Ketua MK harus merangkap sebagai Ketua MA.